2016
DOI: 10.1364/oe.24.023829
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic dual-polarization self-mode-locked Nd:YAG 946-nm lasers: controlling beat frequency and observation of temporal chaos

Abstract: The self-mode-locked (SML) operation at 946 nm can be achieved with a monolithic Nd:YAG crystal when the pump power is above the threshold of the multiple-longitudinal-mode generation. The SML output is further found to include two orthogonal polarization components with a beat frequency coming from the birefringence effect in the laser crystal. The beat frequency can be widely adjusted in the range of 5-220 MHz by controlling the cooling temperature. The present experiment also confirms the theoretical predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Thévenin et al reported a first dual-polarization ML laser with Nd:YAG crystal, synchronously generating two-frequency combs associated with the two polarization eigenstates [24]. Recently, Cheng et al obtained monolithic dual-polarization self-ML Nd:YAG crystal 946 nm lasers with chaotic dynamics and tunable beat frequencies [25,26]. Liang et al reported an orthogonally polarized ML laser with an Nd:YVO 4 crystal, with a wavelength of 1342 nm and pulse repetition rates up to 6.45 GHz [27].…”
Section: µM Vector Mode-locked Pulses From Tm:y O 3 Ceramics Lasermentioning
confidence: 99%
“…Thévenin et al reported a first dual-polarization ML laser with Nd:YAG crystal, synchronously generating two-frequency combs associated with the two polarization eigenstates [24]. Recently, Cheng et al obtained monolithic dual-polarization self-ML Nd:YAG crystal 946 nm lasers with chaotic dynamics and tunable beat frequencies [25,26]. Liang et al reported an orthogonally polarized ML laser with an Nd:YVO 4 crystal, with a wavelength of 1342 nm and pulse repetition rates up to 6.45 GHz [27].…”
Section: µM Vector Mode-locked Pulses From Tm:y O 3 Ceramics Lasermentioning
confidence: 99%